High frequency of low noise amplifier architecture for WiMAX application: A review - Abu Bakar Ibrahim; Che Zalina Zulkifli; Shamsul Arrieya Ariffin; Nurul Husna Kahar (Institute of Advanced Engineering and Science, 2021)
The low noise amplifier (LNA) circuit is exceptionally imperative as it promotes and initializes general execution performance and quality of the mobile communication system. LNA's design in radio frequency (R.F.) circuit requires the trade-off numerous imperative features' including gain, noise figure (N.F.), bandwidth, stability, sensitivity, power consumption, and complexity. Improvements to the LNA's overall performance should be made to fulfil the worldwide interoperability for microwave access (WiMAX) specifications' prerequisites. The development of front-end receiver, particularly the LNA, is genuinely pivotal for long-distance communications up to 50 km for a particular system with particular requirements. The LNA architecture has recently been designed to concentrate on a single transistor, cascode, or cascade constrained in gain, bandwidth, and noise figure.